New Fuzzy ServQual Build with Three Types of Fuzzy Numbers - Wulandari, Ratri; sulistijanti, wellie (Universitas Muhammadiyah Semarang Press, 2022)
Every community in the world desires optimal service quality that meets their expectations. To achieve this, it is essential to measure the level of public satisfaction with the quality of services provided by service providers. Fuzzy servqual is a method used to determine the level of service quality through survey data. The process involves calculating the value of fuzzification, defuzzification, and the GAP value between perception and expectation. This paper introduces a new approach to processing data by using three types of fuzzy numbers: shoulder fuzzy, triangle fuzzy, and trapezoidal fuzzy. The use of three types of fuzzy numbers yields different GAP calculation results compared to using only a triangular fuzzy. The results of this research show that the use of fuzzy number improvement during the fuzzyfication step leads to better GAP results with greater accuracy.